Plunkett's Retail Industry Almanac 2001-2002: The Only Comprehensive Guide to Retail Companies and Trends - Jack W. Plunkett (Texas: Plunkett Research, 2002)
"Plunkett's Retail Industry Almanac 2001-2002" is the third edition of our guide to the retail field, designed to be used as a general source for researchers of all types.
(NP(B/20114s
Keywords: trends -- industry -- companies